PENINGKATAN KEMAMPUAN DAN PENURUNAN TEKANAN DARAH PADA AGREGATE DEWASA HIPERTENSI SESUDAH MENGIKUTI INTERVENSI MODIFIKASI PERILAKU DENGAN HYPNOCARING (MOLUCA) DI CURUG, CIMANGGIS, DEPOK - Indrayanti, Indrayanti; Sahar, Junaiti; Permatasari, Henny (STIKES Bethesda Yakkum, 2018)
Background: Hypertension is an infectious disease problem that continues increase from year to year. Unhealthy lifestyles such as less activity , obesity, consumption of high feed and salt is the main risk factor caused hypertension, need intervention to raised awareness, so hypertension treatment can be maintained so that the pressure can be controlled. Objective: This study aims to determine changes in ability and decrease in blood pressure after Moluca intervention in agregate adult hypertension. Methods: The design of this study uses evidence base practice, data collection by purposive sampling and obtained sample of 58 respondents. Moluca intervention is given for 8 sessions and 1 session in 1 week. Results: The result of Moluca intervention was decreased mean systolic blood pressure 21,16mmHg and diastolic 12,63mmHg.Conclusion: Conclusions Molluca intervention effectively decrease blood pressure with p value: 0.001.Suggestion: Community nurses need to improve their knowledge and skills to develop themselves byparticipating in various trainings for controlling hypertension in community like nursing communityintervention Moluca to improve blood pressure control in agregate adult hypertension.Keywords: Hypertension – Moluca.